2011
DOI: 10.1128/aem.02975-10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medicated Feed on the Development of Antimicrobial Resistance in Bacteria at Integrated Pig-Fish Farms in Vietnam

Abstract: Integrated livestock-fish aquaculture utilizes animal excreta, urine, and feed leftovers as pond fertilizers to enhance the growth of plankton and other microorganisms eaten by the fish. However, antimicrobial-resistant bacteria may be transferred and develop in the pond due to selective pressure from antimicrobials present in animal feed, urine, and feces. In an experimental pig-fish farm located in periurban Hanoi, Vietnam, nine piglets were provided feed containing 5 g of tetracycline (TET)/kg pig weight/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 12 publications
2
41
0
Order By: Relevance
“…This is in agreement with findings reported in a study of some fish ponds in Ghana by Ampofo et al [13] where fish farmers used poultry waste, blood waste, sewage, cow dung and pig dung to fertilise ponds. The use of organic manure by farmers may contribute to antibiotic resistance on the farms by transfer of antibiotic residues and resistant bacteria to fish farms if the commercial farms from which the manure is sourced use antibiotics [9,29,30]. Elsaidy et al [29] in a study of bacterial isolates from water and fish raised in ponds receiving chicken manure recommended the use of fermented chicken manure as a bacteriologically safe fish pond fertilizer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with findings reported in a study of some fish ponds in Ghana by Ampofo et al [13] where fish farmers used poultry waste, blood waste, sewage, cow dung and pig dung to fertilise ponds. The use of organic manure by farmers may contribute to antibiotic resistance on the farms by transfer of antibiotic residues and resistant bacteria to fish farms if the commercial farms from which the manure is sourced use antibiotics [9,29,30]. Elsaidy et al [29] in a study of bacterial isolates from water and fish raised in ponds receiving chicken manure recommended the use of fermented chicken manure as a bacteriologically safe fish pond fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an alarming increase in global reports of antibiotic resistance on fish farms over the years [7,8]. Though some farms do not use antibiotics directly, fish farming practices such as the use of animal manure, waste water, human excreta in fish farms and disposal of untreated effluents from fish farms may contribute to antibiotic resistance in fish farms and adjoining water bodies [9,10]. Ghana has a thriving freshwater aquaculture industry with tilapia and catfish being the most farmed species in freshwater farms with tilapia farming alone contributes 88% of total fish farming in Ghana [11].…”
Section: Introductionmentioning
confidence: 99%
“…Legislation and regulations to control the supply and excessive use of antimicrobials are very poor in many developing Southeast Asian countries (5)(6)(7), and the prevalence of antimicrobial resistance in major bacterial pathogens such as enterococci has been rapidly increasing in Asia (8)(9)(10)(11). In particular, the rise of multidrug-resistant (MDR) enterococci is of great concern.…”
mentioning
confidence: 99%
“…This results in further selection and transfer of antibiotic resistance genes within the microbial community, within in the surrounding environment [38,51]. A study of pigs in VAC systems, revealed high levels of resistance to tetracycline, nalidixic acid and enrofloxacin, among enteric bacteria [52]. This suggests that as a result of exposure to high concentrations of various antibiotics, the risk of colonisation with antibiotic-resistant bacteria and genes increases in the intestinal tracts of livestock.…”
Section: Animal Husbandry and Waste Managementmentioning
confidence: 99%